Study on the Natural Soil Properties Endau Rompin National Park (PETA) as Compacted Soil Liner for Sanitary Landfill - Ahmad, Zulkifli; Mee San, Wong; Damayanti, Alia; Ridzuan, Mohd Baharudin; Daud, Zawawi (International Journal of Integrated Engineering, 2013)
Abstract: This paper reviews and extends an understanding of a study on potential suitability of the natural soil in Endau Rompin National Park (PETA) as a compacted soil liner for sanitary landfill. Since the demand for landfill system becomes obvious so that concerning construction and operation of landfills are increasing. A number of studies have been conducted for the liner system of landfill. Hence, study is required to choose the suitable type of material as liner barrier for the landfill system in term to achieve optimum long term performance. The sanitary landfill plays an important role in the framework of solid waste disposal. The compacted soil liner is a part of a liner structure for landfill to restrict leachate migration from facility into the environment. So that, if the landfill system is not well manage it will contaminate the soil and ground water, thus presenting a risk to human and environmental health. This study, natural soil will be taken from Endau Rompin National Park (PETA), Johor as soil sample for testing. Natural soil is an economy material as a liner system, and it does not decay easily from time to time. So it is an ideal material as a sanitary landfill liner system. In short, the purpose of this study is to compile and organize available information on the use of laboratory testing, as well as providing some guidance on the use of natural soil as barrier layer of landfill and also it suitability of physical and chemical properties natural soil as barrier layer of landfill. Based on the laboratory testing were conducted, found that soil sample taken form Endau Rompin National Park (PETA) is suitable as compacted soil liner for sanitary landfill.